An open conformation of ADAMTS‐13 is a hallmark of acute acquired thrombotic thrombocytopenic purpura. (23rd January 2018) - Roose, E.; Schelpe, A. S.; Joly, B. S.; Peetermans, M.; Verhamme, P.; Voorberg, J.; Greinacher, A.; Deckmyn, H.; De Meyer, S. F.; Coppo, P.; Veyradier, A.; Vanhoorelbeke, K.
Abstract : Essentials Conformational changes in ADAMTS‐13 are part of its mode‐of‐action. The murine anti‐ADAMTS‐13 antibody 1C4 discriminates between folded and open ADAMTS‐13. ADAMTS‐13 conformation is open in acute acquired thrombotic thrombocytopenic purpura (TTP). Our study forms an important basis to fully elucidate the pathophysiology of TTP. Summary: Background: Acquired thrombotic thrombocytopenic purpura (aTTP) is an autoimmune disorder characterized by absent ADAMTS‐13 activity and the presence of anti‐ADAMTS‐13 autoantibodies. Recently, it was shown that ADAMTS‐13 adopts a folded or an open conformation. Objectives: As conformational changes in self‐antigens play a role in the pathophysiology of different autoimmune diseases, we hypothesized that the conformation of ADAMTS‐13 changes during acute aTTP. Methods: Antibodies recognizing cryptic epitopes in the spacer domain were generated. Next, the conformation of ADAMTS‐13 in 40 healthy donors (HDs), 99 aTTP patients (63 in the acute phase versus 36 in remission), 12 hemolytic–uremic syndrome (HUS) patients and 63 sepsis patients was determined with ELISA. Results: The antibody 1C4 recognizes a cryptic epitope in ADAMTS‐13. Therefore, we were able to discriminate between a folded and an open ADAMTS‐13 conformation. We showed that ADAMTS‐13 in HDs does not bind to 1C4, indicating that ADAMTS‐13 circulates in a folded conformation. Similar results were obtained for HUS and sepsis patients. In contrast, ADAMTS‐13 of acute aTTP patients bound to 1C4 in 92% of the cases, whereas, in most cases, this binding was abolished during remission, showing that the conformation of ADAMTS‐13 is open during an acute aTTP episode. Conclusions: Our study shows that, besides absent ADAMTS‐13 activity and the presence of anti‐ADAMTS‐13 autoantibodies, an open ADAMTS‐13 conformation is also a hallmark of acute aTTP. Demonstrating this altered ADAMTS‐13 conformation in acute aTTP will help to further unravel the pathophysiology of aTTP and lead to improved therapy and diagnosis.